Virtue signalling is virtuous - Levy, NL (Springer Science and Business Media LLC, 2020)
The accusation of virtue signalling is typically understood as a serious charge. Those accused usually respond (if not by an admission of fault) by attempting to show that they are doing no such thing. In this paper, I argue that we ought to embrace the charge, rather than angrily reject it. I argue that this response can draw support from cognitive science, on the one hand, and from social epistemology on the other. I claim that we may appropriately concede that what we are doing is (inter alia) virtue signalling, because virtue signalling is morally appropriate. It neither expresses vices, nor is hypocritical, nor does it degrade the quality of public moral discourse. Signalling our commitment to norms is a central and justifiable function of moral discourse, and the same signals provide (higher-order) evidence that is appropriately taken into account in forming moral beliefs.